2020
DOI: 10.3389/fonc.2020.01655
|View full text |Cite
|
Sign up to set email alerts
|

Hsa_circ_0012152 and Hsa_circ_0001857 Accurately Discriminate Acute Lymphoblastic Leukemia From Acute Myeloid Leukemia

Abstract: Acute leukemia (AL) is a group of highly heterogeneous hematological malignancies. Circular RNAs (circRNAs) are covalently closed circRNA molecules implicated in the development of many diseases. However, the role of circRNAs in AL remains largely unknown. Therefore, this study aimed to identify new classification diagnostic biomarkers for subgroups of AL. The circRNA expression signatures discriminating acute lymphoblastic leukemia (ALL) from acute myeloid leukemia (AML) were identified by microarray, followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 56 publications
(59 reference statements)
3
26
0
Order By: Relevance
“…35 Similarly, miR-491-5p was certified to participate in leukemia progression and it was low expressed in ALL cells. 18,36 Similar to this result, miR-491-5p was downregulated in AML tissues and cells in this study. In addition, miR-491-5p expression was negatively related to circ_0009910 level in AML tissues, and miR-491-5p silence could overturn circ_0009910 knockdown-mediated effects on AML cell progression.…”
Section: Discussionsupporting
confidence: 87%
“…35 Similarly, miR-491-5p was certified to participate in leukemia progression and it was low expressed in ALL cells. 18,36 Similar to this result, miR-491-5p was downregulated in AML tissues and cells in this study. In addition, miR-491-5p expression was negatively related to circ_0009910 level in AML tissues, and miR-491-5p silence could overturn circ_0009910 knockdown-mediated effects on AML cell progression.…”
Section: Discussionsupporting
confidence: 87%
“…9,10 For instance, circRAD18 facilitated AML progression through modulating miR-206/PRKACB pathway. 27 Moreover, circ_0012152, derived from RNF220, was demonstrated to be highly expressed in AML tissues relative to normal tissues, 12 but its special molecular mechanism in AML remains largely elusive. Consistent with above research, in this study, circ_0012152 was found to be upregulated in AML, and high circ_0012152 expression was closely related to overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…Sequences of the primers are as follows: MLL-E7, 5 ′ -TACAGGACCGCCAAGAA-3 ′ from exon 7 of MLL; SEPT5-E3, 5 ′ -CAAAGCCTTTCTTCACCGAC-3 ′ from exon 3 of SEPT5; SEPT5-E5, 5 ′ -TGTCCACGATGGTGAGCTTC-3 ′ from exon 5 of SEPT5. About 1 µl cDNA was used for amplification in a total volume of 20 with 0.8 µl of forward primer, 0.8 µl of reverse primer, 10 µl of SYBR Green (Takara, Japan), 0.4 µl of ROX, and 7 µl of RNase-free H 2 O. PCR procedures were carried out as described previously (9). The products were analyzed by electrophoresis with a 1% agarose gel and were then sequenced by the Shanghai Sangong Biotech Corporation (Shanghai, China).…”
Section: Rt-pcr and Sequencing Of Pcr Productmentioning
confidence: 99%